The relationship between vitamin 25(OH)D level and hematological parameters in newly diagnosed women with fibromyalgia syndrome - Aykurt Karlıbel, İlknur; Demirci, Hakan; Kasapoğlu, Meliha; Azkan Türe, Deniz; Altan, Lale (Journal of Surgery and Medicine, 2021)
Background/Aim: Chronic inflammation may play a role in the pathogenesis of fibromyalgia syndrome (FMS). Several hematological markers are prothrombotic, and markers of systemic inflammation. Vitamin D (VitD) level can affect FMS and has an anti-inflammatory effect. The aim of this study is to investigate the relationship between hematological parameters and VitD in FMS and its effect on disease severity. Methods: The prospective case-control study included 90 newly diagnosed female patients with FMS (group 1) and 90 healthy volunteers (group 2). Pain and fatigue were evaluated by visual analogue scale (VAS). Disease severity was evaluated by FMS Impact Questionnaire (FIQ) in FMS. Neutrophils, lymphocytes, platelets, platelet distribution width (PDW) and mean platelet volume (MPV) were obtained from complete blood count results in both groups. Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) were calculated. 25(OH)D concentration was measured. Patients were divided into 3 groups according to vitamin D levels (VitD < 10 ng/ml, 10-30 ng/ml and >30 ng/ml.) Results: The mean MPV and vitamin D levels were significantly higher in group 2 (P=0.001, P<0.001 for both), whereas median PDW was significantly higher in group 1 (P<0.001). Among FMS patients grouped according to VitD levels, only PLR level was significantly different (P=0.049). In subgroup analysis, PLR was significantly higher in the group with VitD < 10 ng/ml compared to the group with vitD levels between 10-30 ng/dl (P=0.024). There was no significant relationship between VitD levels and clinical and laboratory parameters (P>0.05). There was a significant inverse relationship between FIQ and PLR (P=0.022). Conclusion: VitD deficiency may be a risk factor for FMS (cut-off is<14.6 ng/ml). In FMS, high PDW and high PLR in patients with VitD<10 ng/ml are indicative of a prothrombotic condition which can be aggravated by inflammation. We think that complete blood count and VitD levels can support the diagnosis and predict cardiovascular risk in FMS.